MELALUI PERMAINAN TRADISIONAL DITUMBUHKAN SEMANGAT CINTA TANAH AIR - Windu Asmoro; Yummy Jumiati Marsa; Najwa Zahra; Fahma Amelia Harahap; Nazwa Salsabila; Zaki salatin amin Ginting; Ahmad Amanda (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Traditional games are part of cultural heritage that play an important role in instilling national values, particularly the sense of patriotism. However, technological advancement and lifestyle changes have reduced young generations’ interest in traditional games. This study aims to foster patriotism through the implementation of traditional games in Dusun VIII, Timbang Lawan Village, Bahorok District, Langkat Regency. The method used was a participatory and educational approach consisting of preparation, implementation, and evaluation stages. The activities were carried out through various traditional games involving active participation from the community, especially children and adolescents. The results show that traditional game activities can increase community participation and foster values such as cooperation, togetherness, and sportsmanship. Furthermore, the activity raises public awareness about the importance of preserving traditional games as part of cultural identity and as a medium for instilling patriotism.